Evaluating Islamic and Ethical Values in Senior High School PAI Textbooks: Evaluasi Nilai-Nilai Islam dan Etika dalam Buku Teks Pendidikan Agama Islam (PAI) Sekolah Menengah Atas - Fanani, Fuad Dikri; Istikomah, Istikomah (Indonesian Journal of Islamic Studies, 2025)
Background: Islamic Religious Education plays a vital role in shaping students’ character and moral awareness. Specific Background: In the high school context, textbooks serve as the primary medium to instill Islamic values through integrated learning materials. Knowledge Gap: Previous studies often focused on curriculum compliance but rarely examined the alignment between textbook content and moral character formation. Aims: This study aims to analyze the structure, language, and moral values in the Islamic Religious Education and Ethics textbook for Grade X students. Results: Findings indicate that the book aligns well with curriculum standards, presents balanced topics on faith, worship, and ethics, and embeds Islamic values comprehensively. Novelty: The study highlights the integration of character education within Islamic teachings in modern contexts. Implications: The results provide constructive feedback for improving textbook quality to support holistic Islamic education. Highlights:• Evaluation of Islamic education textbooks for high school• Integration of moral and religious values in learning materials• Character formation through Islamic education Keywords: Islamic Education, Textbook Analysis, Character Values, Moral Learning, High School